Outsourcing jako element procesu restrukturyzacji szpitala - Kowalewski, Marcin (Outsourcing as a part of restructuralisation of a Polish hospital, 2006)
There are few reasons to use outsourcing in healthcare: reduce costs and staff, increase productivity and throughput by focusing on core products. This article explains the role of outsourcing in management of Polish hospitals.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 460-465